Green Metrics Evaluation of a Sustainable Ultrasonication-Assisted Routes to Cellulose Ethers from Banana (Musa balbisiana Colla) Blossom Cellulose - Safira Zidna Salama; Venty Suryanti; Maulidan Firdaus; Syafira Narendraduhita (Journal of Multidisciplinary Applied Natural Science, 2026)
To promote sustainable chemical transformation and environmentally friendly approaches, balance economic feasibility and ecological protection are essential. In this study, cellulose ethers, such as methyl cellulose (MC), carboxymethyl cellulose (CMC), and hydroxypropyl cellulose (HPC), were successfully synthesized from banana (Musa balbisiana Colla) blossom cellulose (BBC) through the Williamson ether reaction using a green ultrasonication method at ambient temperature for 30–40 mins. A simple ultrasonic bath system was employed to facilitate efficient cavitation under mild and accessible operating conditions. The yields of MC, CMC, and HPC were 96.5, 98.3, and 97.5%, with corresponding degrees of substitution (DS) of 2.00, 0.71, and 0.86, respectively. An environmental assessment of each synthesis was conducted using Environmental Assessment Tool for Organic Syntheses (EATOS) software and Andraos worksheets, evaluating substrates, solvents, products, and by-products. The results demonstrated that this method offers significant advantages, including low environmental impact, minimal chemical consumption, and near-ideal green chemistry parameters, such as atom economy (AE), reaction yield, stoichiometric factor (1/SF), material recovery (MRP), and reaction mass efficiency (RME), outperforming conventional methods reported in the literature.